Implementation of swarm intelligence algorithms on mobile robots - Kong, Zhung Jie (2017)
This thesis focusses on the implementation of swarm intelligence algorithms on multiple mobile robots. A scenario which could be used to display the swarm intelligence behavior is being designed in this thesis. Positioning or localization of mobile robots is a part of this thesis in order to determine where is the robot position on the field. Wireless communication is conducted between the mobile robots in order to carry out discussion and subsequently solving the problem in a coordinated way without any instructions given by external controller. A target point is set and three paths made from different colours are used to guide the mobile robots towards the target point. Obstacles will be placed randomly at different position on one of the paths created in order to block the robots to go to the target point. Communication between swarm agents is necessary to get a solution for the problem encountered. The result of the experimental setup can be observed in this thesis.